One-Pass In-Band Automatic Bootstrapping for OpenFlow Switches - Chien-Yung Li; Li-Hsing Yen; Kuang-Hui Chi; Chien-Chao Tseng (IEEE Access, 2021)
An SDN switch newly added to a network needs to establish a control channel with an SDN controller to manage control-plane traffic. The setup of such a channel is termed bootstrapping. In the case of in-band control, bootstrapping involves setting up a control path that may traverse one or more switches between the new switch and the controller, which is achieved through the configuration of layer-two to layer-four parameters on relevant switches. Previous approaches either result in lengthy bootstrapping time due to their level-by-level mechanisms, demand complicated modules, or lack some essential features. This paper proposes an approach to fast automatic bootstrapping that overlaps the bootstrapping processes among a set of switches. Our emulations using virtual switches completed the process of bootstrapping 50 switches arranged in a chain in 2.0 seconds, which is a 98% time reduction compared with a prior study.